1H NMR spectra of butane‐1, 4‐diol and other 1, 4‐diols: DFT calculation of shifts and coupling constants. (14th January 2014) - Lomas, John S.
<x xml:space="preserve">Abstract</x> The proton nuclear magnetic resonance (NMR) spectra of butane‐1, 4‐diol, pentane‐1, 4‐diol, (S, S)‐hexane‐2, 5‐diol, 2, 5‐dimethylhexane‐2, 5‐diol and cyclohexane‐1, 4‐diols (cis and trans) in benzene and some other solvents have been analysed. The conformer distribution and the NMR shifts of these diols in benzene have been computed on the basis of the density functional theory, the solvent being included by means of the integral‐equation‐formalism polarizable continuum model implemented in Gaussian 09. Relative Gibbs energies of all conformers are calculated at the Perdew, Burke and Ernzerhof (PBE)0/6‐311+G(d, p) level and NMR shifts by the gauge‐including atomic orbital method with the PBE0/6‐311+G(d, p) geometry and the cc‐pVTZ basis set. Vicinal three‐bond coupling constants for the acyclic diols are calculated from the relative conformer populations, the geometries and generalized Karplus equations developed by Altona's group; these correlate well with the experimental values. The solvent dependence of coupling constants for butane‐1, 4‐diol is attributed to conformational change. Coupling constants for the rigid cyclohexane‐1, 4‐diols do not change with solvent and are readily explained in terms of their geometries. The NMR shifts of hydrogen‐bonded protons in individual conformers of alkane‐1, n‐diols show a very rough correlation with the OH···OH distances. The computed overall NMR shifts for CH protons in 1, 2‐diols, 1, 3‐diols and 1, 4‐diols are systematically high but correlate very well with the experimental values, with a gradient of 1.07 ± 0.01; those for OH protons correlate less well. Copyright © 2014 John Wiley & Sons, Ltd.